The Effect of Using Game-Based Learning Model in History Learning on Students' Interest and Motivation in Athirah Bukit Baruga Islamic High School - Muhammad Aryan Firdaus; Ahmadin Ahmadin; Patahuddin Patahuddin; Bakhtiar Bakhtiar (MASI Mandiri Edukasi, 2026)
History learning in high school often suffers from low student interest and motivation because of teacher-centered, conventional methods that fail to engage the digital generation. This study aims to examine the effect of the Game-Based Learning (GBL) model on students' learning interest and motivation in history at Athirah Bukit Baruga Islamic High School. A quantitative pre-experimental approach with a One-Group Pretest-Posttest Design was employed on 30 purposively selected Class X students. Data were collected using a five-point Likert-scale questionnaire and observational instruments, then analyzed using descriptive statistics, the Kolmogorov-Smirnov normality test, and a paired-samples t-test (α = 0.05) in SPSS. Results showed a significant increase in learning interest (M = 55.73 to M = 85.37) and motivation (M = 57.50 to M = 88.20), both with p = 0.000. Observations confirmed heightened student enthusiasm, collaboration, and interaction. Game-based learning is found to be effective in enhancing students' interest and motivation in history learning.